Implementasi Program Parenting dalam Keterlibatan Orang Tua di Kelompok Bermain Nur Kartika Pertiwi Kec. Jombang Kab. Jombang - Ronalia Haqiqi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to describe the importance of parenting programs reguires the involvement of parents in participating in the activities that have been held and implementing them at home. If education at home and at school are in harmony it will crate a good education for children. Therefore, the importance of parental involvement in schools is able to create the expected student learning outcomes. The main problem is how the Parenting program is Implemented in Play Group Nur Kartika Pertiwi Kec. Jombang Kab. Jombang. The research use a qualitative method with a descriptive approach which is used to describe or depict events or occurrences that occur in the field during the process research at the KB Nur Kartika Periwi Kec. Jombang Kab. Jombang. The informants in this research were divided into two, namely: Key informants the Principal and Educator and Supporting informants the parents of the students. Data collection techbiques observation, interviews and documentation. In implementing the parenting program, the Play Group Nur Kartika Pertiwi Jombang is divided into three stages and parental involvement is divide into six forms. The first stage of implementing the parenting program is Planning the parenting program at the Play Group Nur Kartika Pertiwi Jombang, carrying out five of them, parenting program socialization, equalizing perceptions, identifying needs, determining place time, and preparing program in the Play Group Nur Kartika Pertiwi Jombang, it is carried out by all parties related to the parenting program and carried out in accordance with the program planning that has been determined. Third, the evaluation stage of activities carried out by the Play Group Nur Kartika Pertiwi Jombang uses the focused discussion method. The involvement of parents of students in implementing this parenting program is not all able to attend the parenting program because many parents are prevented from working. So, approximately 50% of the parents of student who take part in the parenting program. However, parents who take part in parenting program are very involved in activities hels at school.
Repo 13 Juli 2026_ Rudy K Finalisasi 13 Juli 2026_Yudi
Keywords: parenting program; parental involvement; play group